Preliminary Remarks on the Crystallization of Magical Consciousness in the Late Middle Ages - Schwartz, Dov (Jewish Thought, 2025)
The article examines a broad distinction between "Ashkenazi magic," which gravitates toward popular or folk practices, and "Sephardic magic," within which rationalist currents incline toward a learned, more scholarly form of magic rooted in scientific thought. It argues that: (a) Conservative groups within the Sephardic and Provençal culturalcontexts wavered between folk magic and learned magic. (b) Rationalist thinkers in these contexts oscillated between endorsinga scientific conception of magic and embracing Maimonides’ uncompromising rejection of it. (c) Jewish creativity in the Ashkenazi regions developed almostexclusively along a spectrum that ranged from varying degrees of folk magic to the radical stance represented in the approach of the author of Sefer Ḥasidim. To substantiate these arguments, the article applies them to a test case: the question of the existence of spiritual entities and the extent to which they were taken into consideration.